Resepsi Al-Qur’an dalam Tradisi Rokat Tase’: Kajian Living Qur’an pada Masyarakat Desa Bandaran Tlanakan Pamekasan - Moh. Samsul Ma'arif; Saidatul Karimah (LPPM IAI Hasanuddin Pare-Kediri, 2026)
This study examines the reception of the Qur’an within the tradition of Rokat Tase’ practiced by the coastal community of Bandaran Village, Tlanakan District, Pamekasan Regency. The research aims to identify the forms of Qur’anic reception embedded in the ritual and to analyze how Qur’anic values are interpreted and practiced in the socio-religious life of the community. This study employs a qualitative approach with a Living Qur’an framework through observation, interviews, and documentation techniques. The findings reveal that the Rokat Tase’ tradition contains various forms of Qur’anic reception, including the recitation of selected Qur’anic verses, collective prayers, and symbolic religious practices intended to seek safety, gratitude, and divine blessing for fishermen and coastal society. The Qur’an functions not only as a sacred text but also as a living cultural guide that shapes social solidarity, spiritual awareness, and local religious identity. The study concludes that the tradition of Rokat Tase’ reflects the dynamic interaction between the Qur’an and local culture, demonstrating that Living Qur’an practices continue to develop contextually within the religious traditions of Madurese coastal communities.